The Feasibility of Interactive Multimedia and Online Quiz Based Gamification on Learning Management System (LMS) Thematic Learning Courses - Tika Aprilia; Amalia Rizki Ardiansyah; Henni Riyanti (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
The global Covid-19 pandemic has had a variety of impacts on the education sector including the deepening of the learning process. The college has transformed initially face-to-face learning activities into distance learning using online learning platform. However, the design of the platform used is still less varied from the type of media and learning applications, where lectures should be able to provoke motivation and the active role of students. This research aims to find out the feasibility results of interactive multimedia and online quiz based on integrated gamification learning system in supporting thematic learning courses. This study used a research and development approach, specifically the ADDIE development model design by Branch (2009). The research subjects are 2nd semester students who will take Thematic Learning courses in Elementary School of Universitas Negeri Yogyakarta and Universitas PGRI Palembang. Data collection techniques use questionnaires and interviews. Data analysis uses descriptive analysis. The results showed that the validation results of media experts obtained a score of 3.88 with good categories and material expert validation obtained a score of 3.89 with a good category. Then the results of student responses to interactive multimedia products and online quiz based gamification at the time of the limited trial which included one to one trial obtained a score of 3.50 with a good category, small group trail obtained a score of 3.69 with a good category, and the field trial received a score of 3.95 with an very good category. Thus interactive multimedia and online quiz based gamification integrated LMS in thematic learning courses are said to be feasible and can be used in increasing student motivation and interaction in the lecture process.